2020
DOI: 10.1145/3428240
|View full text |Cite
|
Sign up to set email alerts
|

A modular cost analysis for probabilistic programs

Abstract: We present a novel methodology for the automated resource analysis of non-deterministic, probabilistic imperative programs, which gives rise to a modular approach. Program fragments are analysed in full independence. Moreover, the established results allow us to incorporate sampling from dynamic distributions, making our analysis applicable to a wider class of examples, for example the Coupon Collector's problem. We have implemented our contributions in the tool eco-imp, exploiting a constraint-solver over ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…2 Via a telescoping-sum argument, it can be shown that ecost ( ) coincides with the mean cost emitted along all probabilistic reduction paths, compare e.g. [Avanzini et al 2020], thereby matching its intended meaning. In a similar spirit, nf : Λ → D(V ) can be defined as the least function such that:…”
Section: The Non-pure Fragmentmentioning
confidence: 97%
See 2 more Smart Citations
“…2 Via a telescoping-sum argument, it can be shown that ecost ( ) coincides with the mean cost emitted along all probabilistic reduction paths, compare e.g. [Avanzini et al 2020], thereby matching its intended meaning. In a similar spirit, nf : Λ → D(V ) can be defined as the least function such that:…”
Section: The Non-pure Fragmentmentioning
confidence: 97%
“…Operational Semantics. In order to capture the two effects, probabilistic sampling and cost, we express the operational semantics of the language Λ by a (probabilistic) reduction relation − − → ⊆ D(Λ )×R +∞ ×D(Λ ), defined through a (weighted) probabilistic abstract reduction system [Avanzini et al 2020;Bournez and Garnier 2005] over terms Λ . Triples ( , , ) ∈ − − →, written as − − → , signify that the term distribution evolves in one-step to a reduct-distribution , producing an expected cost equal to .…”
Section: The Non-pure Fragmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the authors also investigate lower bounds on expected runtimes and tail-probabilities, topics not covered in our work. 1 While it is possible to translate such programs into probabilistic term rewrite systems [4], our method will not capture typical termination arguments on probabilistic integer programs, since properties of integers will be unavailable after the encoding. 2 We thank Luis María Ferrer Fioriti for this analysis.…”
Section: Related Workmentioning
confidence: 99%
“…These methods have lent themselves to various generalisations, including polynomial programs, programs with non-determinism, lexicographic and modular termination arguments, and persistence properties [2,[14][15][16]20,25]. Recently, for special classes of probabilistic programs or term rewriting systems, novel automated proof techniques that leverage computer algebra systems and satisfiability modulo theories (SMT) have been introduced [5,6,38,39,41]. All the above methods are sound and, under specific assumptions, complete; they represent the state of the art for the class of programs they have been designed for.…”
Section: Introductionmentioning
confidence: 99%